Examining the Impact of Innovation in Research and Development on SME Employability: An Econometric Analysis in Morocco: - BARI Yasmina; LAMZIHRI Othmane; AZEGAGH Jalal; EL KAMLI Mohammed (African Scientific Journal, 2023)
This study examines the relationship between technology-focused research and development (R&D) investment and the employability of small and medium-sized enterprises (SMEs) in the context of Morocco. Using an econometric analysis based on the Autoregressive Distributed Lag (ARDL) model, we investigate the impact of R&D investment and the presence of advanced technology on SME employability. The study also explores the differential employability outcomes for SMEs receiving government support for technology-related R&D. The findings of our study contribute to the existing literature by providing empirical evidence on the relationship between technology-focused R&D investment and SME employability in the Moroccan context. The results indicate a significant positive association between R&D investment and SME employability, highlighting the importance of technological advancements in enhancing job opportunities within the SME sector. Additionally, the analysis reveals that government support for technology-related R&D has a notable impact on SME employability, emphasizing the effectiveness of such policies in fostering employment growth. The implications of our research are valuable for policymakers, industry practitioners, and SME stakeholders. The findings can inform evidence-based decision-making processes and the formulation of targeted policies aimed at promoting sustainable economic development and improving employability outcomes for SMEs in Morocco. By aligning R&D investment strategies and technology adoption efforts with the goal of enhancing employability, policymakers can create an enabling environment that nurtures SME growth and competitiveness.